The Lippincott- Raven internal medicine interactive text and review (Philadelphia : Lippincott- Raven, 1997)
(Producer) Features complete text and illustration from Kelley,3/e, state-of-art color graphic and windowing features, clik-search by word, phase, topic or contributor,'Rapid Access' features for key points on common diseases, hyperlinks, cross-checks, and print capabilties, interactive, sefl-test version of Schlossberg's Review of Internal Medicine with over 1,100 exam review question.
CD is available at Koleksi Media, Perpustakaan HUKM
Links with the encyclopedic coverage of Kelley's Textbook of Internal Medicine, Third Edition, the quick reference Rapid Access Guide, and Schlossberg's Review of Internal Medicine.
System requirements: Windows 3.1 or higher; 8MB of RAM; 11MB of free hard disk space
System requirements: Systems 7.1 or higher; Macintosh; 8MB of RAM; 8MB of free hard disk space
Keywords: Internal Medicine -- CD-ROM